Investigation of Venus cloud aerosol and gas composition including potential biogenic materials via an aerosol-sampling instrument package - Baines, KH; Nikolić, D; Cutts, JA; Delitsky, ML; Renard, J-B; Madzunkov, SM; Barge, LM; Mousis, O; Wilson, C; Limaye, SS; Verdier, N (Mary Ann Liebert, 2021)
A lightweight, low-power instrument package to measure, in situ, both (1) the local gaseous environment and (2) the composition and microphysical properties of attendant venusian aerosols is presented. This Aerosol-Sampling Instrument Package (ASIP) would be used to explore cloud chemical and possibly biotic processes on future aerial missions such as multiweek balloon missions and on short-duration (<1 h) probes on Venus and potentially on other cloudy worlds such as Titan, the Ice Giants, and Saturn. A quadrupole ion-trap mass spectrometer (QITMS; Madzunkov and Nikolić, J Am Soc Mass Spectrom 25:1841–1852, 2014) fed alternately by (1) an aerosol separator that injects only aerosols into a vaporizer and mass spectrometer and (2) the pure aerosol-filtered atmosphere, achieves the compositional measurements. Aerosols vaporized <600°C are measured over atomic mass ranges from 2 to 300 AMU at <0.02 AMU resolution, sufficient to measure trace materials, their isotopic ratios, and potential biogenic materials embedded within H2SO4 aerosols, to better than 20% in <300 s for H2SO4 -relative abundances of 2 × 10−9. An integrated lightweight, compact nephelometer/particle-counter determines the number density and particle sizes of the sampled aerosols.